2002
DOI: 10.1046/j.1440-6047.11.s1.1.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural aspects of the aged: A case study in Indonesia

Abstract: In the year 2020, the life expectancy in Indonesia will be 71.7 years and the proportion of older people will be between 10 and 11% or 30 million persons. Presently, older men are mostly married, while older women are mostly divorced. Older men are the heads of the household, while older women are spouses or parents in the household. Older women mostly do not have any formal education, while older men have primary and intermediate education. Older men are mostly literate, while older women are illiterate. Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The study showed older informants' conceptualized opinions were based mainly on their sociocultural, socioeconomic and sociogeographical backgrounds. This study was later published (Abikusno and Kusumaratna 2002 ). In the same year Dr Abikusno was also assigned by the UNFPA to facilitate the fi rst edition of the National Plan of Action (NPA) for Older Persons' Welfare and subsequent editions until the present NPA on Older Persons' Welfare period of 2009-2014.…”
Section: The Inresage Trisakti University Research Institutementioning
confidence: 99%
“…The study showed older informants' conceptualized opinions were based mainly on their sociocultural, socioeconomic and sociogeographical backgrounds. This study was later published (Abikusno and Kusumaratna 2002 ). In the same year Dr Abikusno was also assigned by the UNFPA to facilitate the fi rst edition of the National Plan of Action (NPA) for Older Persons' Welfare and subsequent editions until the present NPA on Older Persons' Welfare period of 2009-2014.…”
Section: The Inresage Trisakti University Research Institutementioning
confidence: 99%
“…Other studies related to the health conditions of older Indonesians found that rural aged are predominantly female and significantly older than the urban aged (above 80 years), mostly live alone, are socio-economically disadvantaged, and they experience chronic illnesses and degenerative diseases such as rheumatoid arthritis, hypertension, eye complaints and impaired vision, and have stomach problems (Abikusno 2002(Abikusno , 2007Van Eeuwijk 2006).…”
Section: The Health Status Of Older Peoplementioning
confidence: 99%
“…J. 3 (1): 1-7, 2012al., 1990Poon et al, 1992;Macigilian et al, 1993;Kumar, 1996;Abikusno, 2002) and on the Indian Hunter-Gatherers (Kurichias) (Ramachandran, 2004). This exercise enabled the researchers to pickup several relevant variables that are likely to contribute for longevity.…”
Section: Determinants Of Longevity: An Analysismentioning
confidence: 99%